Climate Legal Mobilization Under the New Aarhus Regulation - Mario Pagano (German Law Journal)
The present contribution seeks to provide an empirical overview of how the amended internal review mechanism established under the EU Aarhus Regulation is currently being deployed by civil society organizations to mobilize EU climate change law. This Article argues that the 2021 reform of the Aarhus Regulation has broadened the legal opportunity structure available to environmental organizations, which can now challenge a much broader set of EU administrative acts. However, this contribution holds that the internal review mechanism is being used strategically by environmental NGOs with the intention to contest - even before the EU judiciary - not only EU administrative acts, but also broader policy arrangements, representing the legal infrastructure of the EU ecological transition. In this regard, the Aarhus internal review mechanism can now be considered a real scientific dispute settlement forum, where NGOs and EU institutions can confront each other and disagree on the way scientific evidence is taken into account in the EU policymaking. Finally, the new specific features of the internal review mechanism are truly empowering only those organizations owning the necessary legal and technical expertise, allowing such NGOs to act as credible scientific interlocutors of the EU institutions on behalf of the wider public.